الحماية القانونية لأقلية المساهمين من مخاطر الاستحواذ - هادي, علي طلال (Journal of Legal Sciences, 2017)
Contributing companies consist mainly of two categories of shareholders: the majority and the minority. The first category (majority shareholders) means the controlling shareholders of the companies capital and its board of directors and voting at its general assembly meetings without the second category (minority shareholders), especially the acquisitions and risks to the company. We find that the Egyptian legislator has created legal protection for a minority of these risks, by forcing the acquiring party to make a mandatory purchase offer for the remaining shares in the company, at least the highest rate of acquisition of the capital of the company, Nahina on the application of the principles of corporate governance and its importance to protect minority shareholders, because they provide equality of rights and equality, including the protection of the interests of the company and its clients.The research did not limit the legal protection of the minority shareholders against the of acquisitions, but rather highlighted the need to protect the agreement between the shareholders of the company, to protect the minority of them, to support and increase trust and preserve the company's reputation. Competition for personal party wishing to acquire, as well as the possibility of the company's capital increase in order to block the acquisition, and some other appearances. In light of the foregoing, the Iraqi legislator did not provide any protection to the minority shareholders except as provided in the provisions of paragraph (3) of section (10) of CPA order No. (74) of 2004 stipulating the protection of the minority shareholders by obligating the acquirer ratio (30%) for any contribution listed on the Iraq Stock Exchange company, the disclosure of its ownership in the company's capital, without creating any protection of minority shareholders, unlike the Egyptian legislator real solutions. So we hope the Iraq legislature to find a legislative organization within the Security Market Law for the purpose of protecting minority shareholders from the risk of acquiring similar to the Egyptian legislator.